Chronic cystoisosporiasis in an immunocompetent adult: A case report - Ohno, Masashi; Inatomi, Osamu; Imai, Takayuki; Takahashi, Kenichiro; Bamba, Shigeki; Konishi, Keiji; Sasaki, Masaya; Kushima, Ryoji; Andoh, Akira (Medicine (Baltimore), 2021)
Cystoisosporiasis is an intestinal infectious disease caused by a coccidian protozoa, Cystoisospora belli (C. belli). It can cause prolonged and refractory diarrhea most commonly in immunocompromised patients, while immunocompetent individuals usually exhibit no symptoms or self-limited diarrhea. We herein report a case of chronic cystoisosporiasis in an immunocompetent patient. A 62-year-old man, who had been first diagnosed with cystoisosporiasis 15 years ago and had been treated with oral administration of trimethoprim-sulfamethoxazole (TMP-SMX), complained of persistent watery diarrhea. He was negative for anti-human immunodeficiency virus antibody and anti-human T-cell leukemia virus type 1 (HTLV-1) antibody. Biopsy specimens from the duodenum revealed oocysts in the atrophic absorptive epithelium and protozoa were detected through stool examination, indicating the recurrence of cystoisosporiasis. Capsule endoscopy showed diffuse atrophic mucosa with white villi in the entire small intestine. We diagnosed him with chronic cystoisosporiasis that occurred in an immunocompetent adult. Since oral administration of TMP-SMX and ciprofloxacin were ineffective, the intravenous administration of TMP-SMX was initiated. Intravenous TMP-SMX exhibited a significant improvement. This case indicates that even immunocompetent individuals may develop recurrent and refractory cystoisosporiasis. Furthermore, intravenous treatment of antibiotic agents should be considered when the impaired absorptive ability from the small intestine is suspected.